Statactivism against the penal machinery in the aftermath of “1968”: The Case of the French Groupe d’Information Sur les Prisons - Grégory Salle (Coordinamento SIBA, 2014)
The action of the French Groupe d’information sur les prisons (GIP) in the early 1970s has recently been characterized as “optical activism”. By analogy, this article considers the activist efforts of the GIP from the angle of statistical activism or “statactivism”. It assumes that there is something to be gained from re-examining the GIP’s activities from this perspective on the assumption that, because prison was —particularly at that time— a place of deprivation and scarcity, it was a world in which quantities, however low they may have been, did count. Quantification was not the most important of the GIP’s wide range of activities; yet it was crucial under certain circumstances, or for addressing certain issues: if information was "a weapon" (a watchword of the group), then statistical information was no exception to the rule. Emphasizing the issues of prison suicides and class justice, this article reviews different practices of statactivism, from challenging official figures to resorting to an original quantification operation. If the GIP paved the way for a critique that is now commonplace, it has also brought about a decisive and paradoxical shift, by which citing numbers no longer only answered the conventional quantitative question “how many?” (how many prisoners?), but also answered the qualitative and more disturbing question “who?”: who are the prisoners?